Family-led rehabilitation after stroke in India: the ATTEND trial, study protocol for a randomized controlled trial - Alim, Mohammed; Lindley, Richard; Felix, Cynthia; Gandhi, Dorcas Beulah Chandramathy; Verma, Shweta Jain; Tugnawat, Deepak Kumar; Syrigapu, Anuradha; Anderson, Craig Stuart; Ramamurthy, Ramaprabhu Krishnappa; Langhorne, Peter; Murthy, Gudlavalleti Venkata Satyanarayana; Shamanna, Bindiganavale Ramaswamy; et al. (BioMed Central, 2016)
Background: Globally, most strokes occur in low- and middle-income countries, such as India, with many affected people having no or limited access to rehabilitation services. Western models of stroke rehabilitation are often unaffordable in many populations but evidence from systematic reviews of stroke unit care and early supported discharge rehabilitation trials suggest that some components might form the basis of affordable interventions in low-resource settings. We describe the background, history and design of the ATTEND trial, a complex intervention centred on family-led stroke rehabilitation in India. Methods/design: The ATTEND trial aims to test the hypothesis that a family-led caregiver-delivered home-based rehabilitation intervention, designed for the Indian context, will reduce the composite poor outcome of death or dependency at 6 months after stroke, in a multicentre, individually randomized controlled trial with blinded outcome assessment, involving 1200 patients across 14 hospital sites in India. Discussion: The ATTEND trial is testing the effectiveness of a low-cost rehabilitation intervention that could be widely generalizable to other low- and middle-income countries.